(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The purpose of the study is to identify the factors that influenced the formation and development of ideas about the concept of "physical culture" in English-speaking countries. Research results and conclusions. The authors continue to study the circumstances of the origin and evolution of the concept of "physical culture". The reconstruction is carried out by studying the etymology of the term, followed by a historical overview of the ideas that formed the concept in English-speaking countries. The authors show that the representation physical culture developed in accordance with changes in social relations from the first half of the 19th to the middle of the 20th centuries. Having arisen as a result of the cultural transformations of the Enlightenment, physical education reflected the essence of the humanistic tradition of educating a person in striving to physical, spiritual and moral self-improvement. The further evolution of ideas about physical culture was associated with its role in strengthening individual and public health, rational rest, military connotations, ideas about the beauty of a well-developed body and the commercialization of attitudes towards it, and also racial and eugenic theories. In the twentieth century, physical culture developed within the framework of specific states, reflecting their respective national policies. In the conclusion of the article, possible further directions for the analysis of the concept of "physical culture" are determined.